Culture and Conflict Resolution in Cross-Cultural Projects: Insights from Questionnaires and Interviews - Wang, Shihong; Lyu, Junpeng; Pitt, Michael (Journal of Intelligent Decision Making and Information Science, 2024)
As conflict management gained more importance in cross-cultural project management, this paper explores conflicts and conflict resolution strategies in real-world cross-cultural projects, emphasizing the significant influence of cultural differences. Conducting a mixed-method approach that combines questionnaires and interviews, this study identifies various types of conflicts: communication conflicts, cooperation conflicts, value conflicts, status conflicts, and relationship conflicts. Then, this paper classifies conflict resolution strategies according to five conflict management styles: competing, cooperating, compromising, avoiding, and accommodating. The findings reveal that cultural differences can have dual effects on cross-cultural project dynamics. While they can lead to conflicts and challenges, they also present opportunities for growth and innovation. The results, supported by data from prior studies in cross-cultural projects, demonstrate that understanding and managing these conflicts is crucial for project success. Furthermore, the study’s findings are generally valid and potentially transferable across different contexts within project management despite some limitations, such as a smaller sample size and a focus on internal rather than external conflicts. This research contributes to academic knowledge and practical applications, offering insights for improving conflict resolution strategies and enhancing cross-cultural collaboration in project management. Future research could address the identified limitations by expanding the scope of the study and focusing more on external conflicts and specific situational dynamics.